1981
DOI: 10.5962/bhl.title.5313
|View full text |Cite
|
Sign up to set email alerts
|

Introduction and index to Fieldiana: Geology volume 33 / Eugene S. Richardson, Jr. -- William D. Turnbull --.

Abstract: Brachipposideros 65 Bradyodonti evolution 521 tooth histology 523 Brain condylarth 323 notoungulate 416 Bridgerian 574 Brittsia problematica 315 Burrows, Permo-Carboniferous 271 Callianassa 288 Calycocoelia 9 Campodus 532 Canis lupus 145 Capra hircus aegagrus 145 Capra ovis, indet. 145 Caproberyx 363 superbus 367 Carinodens fraasi 237 Carodnia 409 Carolozittelia 397 ''eluta'' 409 tapiroides 409 Cephalopoda Mississippian Rayonnoceras 511 Ceratodus parvus 47 Cervus elaphus 145 Chelonia, Chelydridae,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…In all the cases that have been considered in this study, the correlation coef cient was never below 0.99, even for rare events. This result con rms those obtained by Richardson (2000) for EPS-based probabilistic forecasts of precipitation amounts and 850 hPa temperature anomaly. There exists consistent empirical evidence from a number of studies that the bi-normal model allows an excellent t of ROC curves built from probabilistic weather forecasts (Mason 1982).…”
Section: Estimation Of Reliability Through a Statistical Schemesupporting
confidence: 53%
See 1 more Smart Citation
“…In all the cases that have been considered in this study, the correlation coef cient was never below 0.99, even for rare events. This result con rms those obtained by Richardson (2000) for EPS-based probabilistic forecasts of precipitation amounts and 850 hPa temperature anomaly. There exists consistent empirical evidence from a number of studies that the bi-normal model allows an excellent t of ROC curves built from probabilistic weather forecasts (Mason 1982).…”
Section: Estimation Of Reliability Through a Statistical Schemesupporting
confidence: 53%
“…Although further experiments have con rmed previous results obtained by Richardson (2000) about the appropriateness of the bi-normal model for tting ROC curves in the case of precipitation forecasts, the method might still prove irrelevant for other meteorological variables, other domains and other periods of time than those considered in the present study.…”
Section: Discussionmentioning
confidence: 44%
“…The inclusion of either a second model or a second analysis improved the ensemble skill, but the greatest bene t resulted from using both models and analyses. Richardson (2001) found that especially the use of different operational analyses was bene cial for de ning an ensemble strategy; the additional bene ts of including different models was less clear.…”
Section: Forcing Linear Models: Two Applicationsmentioning
confidence: 99%
“…The conformation of residues Arg42 -His45 is defined by a large number of NOES, a number of which are unusual (most notably Cys43 CI to Arg42 NH and Cys43 a to Val39 a), and a unique set of dihedral angles are produced (see Table 5 ) which can be characterised, following Efimov (1986), as yR, xL, yR, /I. The section Glu44-His45 closely resembles a classic /I-bulge (Richardson et al, 1978), with Val39 acting as the control residue. This is supported by the frequent observation of hydrogen bonds from Glu44-NH and His45-NH to Va139-0 in dynamics simulations (see below) and the fact that the side chains of Va139, Glu44 and His45 are all on the same side of the P-sheet.…”
Section: Backbone Conformationmentioning
confidence: 99%